This is a standard property of localizations:

**Theorem.** Let $R$ be a commutative ring, and let $S\neq\emptyset$ be a multiplicative subset. Let $M$ be an $R$-module. Let $\varphi\colon R\to S^{-1}R$ be the canonical map ($\varphi(r) = \frac{rs}{s}$), and likewise, by abuse of notation, let $\varphi\colon M\to S^{-1}M$ be the natural map $(\varphi(m) = \frac{sm}{s}$ with $s\in S$).

For every submodule $N$ of $M$, $S^{-1}N = \{\frac{a}{s}\mid a\in N\}$ is a submodule of $S^{-1}M$.

If $L$ is a submodule of $S^{-1}M$, then $\varphi^{-1}(L) = \{m\in M\mid \varphi(m)\in L\}$ is a submodule of $M$.

If $N$ is a submodule of $M$, then $N\subseteq \varphi^{-1}(S^{-1}N)$. Moreover, if $N=\varphi^{-1}(L)$ for some submodule $L$ of $S^{-1}M$, then $L=S^{-1}N$.

*Proof.* $S^{-1}N$ is nonempty, as it contains $\frac{0}{s}$; it is closed under differences, since $\frac{a}{s}-\frac{b}{t} = \frac{ta-sb}{st}\in S^{-1}N$ if $a,b\in N$. And it is closed under scalar multiplication, since $a\in N$ implies $ra\in N$ for all $r\in R$, so $\frac{r}{t}(\frac{a}{s}) = \frac{ra}{ts}\in S^{-1}N$ if $a\in N$.

Now let $L$ be a submodule of $S^{-1}M$; since $\varphi$ is a module homomorphism, the pullback of a submodule is a submodule, so 2 is immediate.

Again, let $N$ be a submodule of $M$. Then for every $a\in N$ we have
$\varphi(a) = \frac{sa}{s}\in S^{-1}N$, since $sa\in N$, hence $a\in \varphi^{-1}(S^{-1}N)$. Now assume that $N=\varphi^{-1}(L)$. If $a\in N$ and $s\in S$, then $\frac{a}{s} = \frac{ssa}{sss} = \frac{s}{ss}\frac{sa}{s} =\frac{s}{ss}\varphi(a)\in L$ (since $\varphi(a)\in L$), hence $S^{-1}N\subseteq L$. Conversely, let $\frac{m}{t}\in L$. Then $\frac{tt}{t}\frac{m}{t} = \frac{(tt)m}{tt}=\varphi(m)\in L$, hence $m\in \varphi^{-1}(L) = N$; thus, $\frac{m}{t}\in S^{-1}N$, proving that $L\subseteq S^{-1}N$. Therefore, $L=S^{-1}N$, as claimed. $\Box$

**Corollary.** Every submodule of $S^{-1}M$ is of the form $S^{-1}N$ for some submodule $N$ of $M$.